Research Progress of Traditional Chinese Medicine in the Treatment of IBS-D and Bile Acid-intestinal Flora Imbalance - Shi, Lijun; Han, Jian; Zhang, Xi (Journal of Contemporary Medical Practice, 2025)
Irritable bowel syndrome with diarrhea (IBS-D) is a common functional bowel disease, and its pathogenesis is closely related to the imbalance of intestinal flora-biliary acid metabolism axis. Studies have shown that IBS-D patients generally have abnormal bile acid metabolism and intestinal flora imbalance, which aggravate intestinal barrier damage, visceral hypersensitivity and diarrhea symptoms through interaction. Based on the core pathogenesis theory of ‘liver depression and spleen deficiency’, traditional Chinese medicine shows unique advantages in the treatment of IBS-D by synergistically regulating the function of bile acid-intestinal flora axis through multiple targets. Mechanism studies have shown that soothing liver and invigorating spleen prescriptions (such as Tongxie Yaofang and Xiaochaihu Decoction) can repair bile acid enterohepatic circulation and reduce serum abnormal bile acid levels. Spleen-invigorating and dampness-removing prescriptions (such as Gegen Qinlian Decoction) reshape the flora structure and increase the abundance of beneficial bacteria such as Bifidobacterium by regulating inflammatory factors such as IL-10 and TNF-α. In addition, acupuncture, moxibustion and other external therapies improve bile acid secretion by regulating the brain-gut axis and 5-HT signal. The existing evidence shows that traditional Chinese medicine can synergistically restore the homeostasis of flora and the balance of bile acid metabolism through the ‘multi-component-multi-target’ comprehensive regulation mode, which provides new ideas for the treatment of IBS-D. In the future, it is necessary to deepen the mechanism research, clarify the active components of traditional Chinese medicine and the host-microorganism interaction network, and promote the development of precision treatment.